The Neural Basis of Moral Judgement for Self and for Others: Evidence From Event-Related Potentials - Jiang, Qin; Zhuo, Linglin; Wang, Qi; Lin, Wenxia (Frontiers in Human Neuroscience, 2022)
Developmental and neuroscience works have demonstrated that the moral judgement is influenced by theory of mind (ToM), which refers to the ability to represent the mental states of different agents. However, the neural and cognitive time course of interactions between moral judgement and ToM remains unclear. The present event-related potential (ERP) study investigated the underlying neural substrate of the interaction between moral judgement and ToM by contrasting the ERPs elicited by moral judgements for self and for others in moral dilemmas. In classic moral dilemmas, the agents must choose between the utilitarian choice (taking the action to kill or harm an innocent person but saving more people) and the non-utilitarian choice (taking no action to kill or harm the innocent person but letting some people die). The ERPs were recorded from participants who made moral judgements for self and for others when the agent made utilitarian or non-utilitarian choices during the dilemma. The results revealed that the moral judgement for others elicited a larger frontal late positive component (LPC, 500-900 ms) than that for self when the agents made utilitarian choices, while no difference was observed on early components of N1, P2, and N2. Moreover, individual differences in mentalising ability were negatively correlated with the LPC amplitudes. These findings suggested that ToM modulated the late controlled process but not the early automatic process during moral judgements.